Seasonality Affects the Diversity and Composition of Bacterioplankton Communities in Dongjiang River, a Drinking Water Source of Hong Kong - Sun, Wei; Xia, Chunyu; Xu, Meiying; Guo, Jun; Sun, Guoping (Frontiers in Microbiology, 2017)
Water quality ranks the most vital criterion for rivers serving as drinking water sources, which periodically changes over seasons. Such fluctuation is believed associated with the state shifts of bacterial community within. To date, seasonality effects on bacterioplankton community patterns in large rivers serving as drinking water sources however, are still poorly understood. Here we investigated the intra-annual bacterial community structure in the Dongjiang River, a drinking water source of Hong Kong, using high-throughput pyrosequencing in concert with geochemical property measurements during dry and wet seasons. Our results showed that Proteobacteria, Actinobacteria, and Bacteroidetes were the dominant phyla of bacterioplankton communities, which varied in composition and distribution from dry to wet seasons and exhibited profound seasonal changes. ActinobacteriaBacteroidetes and Cyanobacteria seemed to be more associated with seasonality that the relative abundances of Actinobacteria and Bacteroidetes were significantly higher in the dry season than those in the wet season (p<0.01), while the relative abundance of Cyanobacteria was about tenfold higher in the wet season than in the dry season. Temperature and NO3--N concentration represented key contributing factors to the observed seasonal variations. These findings help understand the roles of various bacterioplankton and their interactions with the biogeochemical processes in the river ecosystem.